Phytochemical Investigation and Evaluation of Analgesic Activity of Passiflora edulis Linn Leaves Available in South Eastern Odisha - Panda, Sangram Keshari (International Journal of Pharmaceutical & Biological Archive, 2012)
Phytochemical Investigation and Evaluation of Analgesic Activity of Passiflora edulis Linn Leaves Available in South Eastern Odisha